Effectiveness of Tui Na Massage on Eating Frequency in Batita Children at The Working Area of Lubuk Alung Puskesmas, Padang Pariaman District, 2020 - Fetrisia, Wiwit; Mulia, Gelisma; Rahmadheny, Suci (Rajaki of Tulip Medika Publisher, 2023)
Background: Children's health needs attention, especially children who don't like to eat so they need direction to increase their appetite. Children who are stunted due to lack of food intake and recurrent diseases, especially infectious diseases that can increase metabolic needs and reduce appetite. Objective: To know the effectiveness of tui na massage on eating frequency in children Methodology: This type of research is Quasy Experiment with One-Group Pretest-Post-Test design, namely the grouping of experimental groups. This study examines the changes that occur in groups after the experiment (treatment). Result: The research results showed that there was a relationship between nutritional status (p= 0,013), years of work (p= 0,026), smoking habits (p= 0,026), and the physical environment (p=0,005) with a length of work. The results showed that the average frequency of eating toddlers before the Tui Na massage intervention was 1.33, the average frequency of eating toddlers after the Tui Na massage intervention was 2.33, there were differences in the frequency of toddler eating by Tui Na massage interventions and which is not done Tui Na massage intervention, less effective Tui Na massage is done to increase the frequency of feeding on toddlers. Conclusion: Based on the results of this research, it can be concluded that there is a relationship between nutritional status, length of service, smoking habits, and the physical environment and job satisfaction among workers.